Application of Analytic Hierarchy Process (AHP) Method in Comparing Stakeholder Perceptions of Tourism Impact in Mentawai Islands - Andika, Rifan; Subanu, Leksono Probo (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Tourism has become one of the important industries in the Mentawai Islands. Some people depend on the tourism sector. The tourism sector does not come without any consequences or impacts, both positive and negative. Each tourism stakeholder has a perception of the tourism impact. It is necessary to trace stakeholders’ perceptions of the impact of tourism on a tourist destination so that these perceptions can be a reference in tourism development that can represent the interests of all parties. This study explored stakeholder perceptions of tourism impact in the Mentawai Islands. The stakeholders studied in this study are local governments and local communities. This quantitative research used the Analytic Hierarchy Process (AHP) approach to obtain priority impacts from both stakeholder groups. Analyzing stakeholder perceptions seldom use the AHP method. The method is different from quantitative methods in general. A mathematical approach determines stakeholder perceptions of tourism impacts instead of statistical approaches. The tourism impact focused on three main impacts, i.e., economic, socio-cultural, and environmental impacts. The study shows that local governments' perceptions of the tourism impact are dominant in the economic impact (40.14%). Meanwhile, the local community’s perceptions tend to the environmental impact (40.24%). When compared, several impact criteria are considered equally important by both stakeholder groups. Based on this, the comparison of these two stakeholder perceptions can be a reference in the development of tourism in the Mentawai Islands.